Digital Transformation and Institutional Framework of E-Commerce in Uzbekistan - Kurpayanidi, Konstantin (International Journal of Business, Law, and Education, 2025)
In the context of accelerating global digitization, electronic commerce (e-commerce) has emerged as a transformative engine for economic growth, social progress, and international integration, particularly in emerging economies like Uzbekistan. This study investigates the institutional environment underpinning e-commerce development in Uzbekistan, a nation strategically leveraging digital transformation to enhance its global economic presence. Despite notable progress in legislative reforms, digital infrastructure, and state-led initiatives supporting small and medium enterprises (SMEs), the scalability and resilience of Uzbekistan’s e-commerce sector remain constrained by institutional gaps, including regulatory inconsistencies, infrastructural disparities, and limited digital literacy. Employing a mixed-method approach—integrating systemic analysis, statistical modeling, expert evaluations, and comparative benchmarking with global best practices—this research delineates the critical institutional mechanisms required to catalyze e-commerce growth. Findings reveal that a robust institutional framework, encompassing adaptive legislation, reliable infrastructure, and stakeholder trust, is indispensable for enhancing economic efficiency, competitiveness, and inclusivity. Uzbekistan’s experience offers a valuable case study for transitional economies, highlighting the interplay between policy innovation, market readiness, and societal adaptation. The study contributes actionable insights for policymakers and enriches the scholarly discourse on digital economy institutionalization.